The Role of Village Institutions in Participatory Development Planning - Ridwan Syam; Atma Ras; Nuvida Raf; Hariashari Rahim; Moh. Dwi Angga Suparman (International Journal of Qualitative Research, 2022)
Development essentially has a goal that is none other than to create a just, prosperous and prosperous society. In advancing the development of rural communities, village institutions have an important role that can assist the implementation of the process of forming a prosperous society. This study aims to determine the role of village institutions in participatory development in Samaenre Village, Maros Regency. The method in this study uses a qualitative descriptive approach with data collection techniques through direct observation, in-depth interviews, and FGD. Determination of informants was carried out using the purposive sampling technique with 6 informants. The results showed that there were several village institutions located in Samaenre Village, Mallawa District, Maros Regency, namely the Village Government, Polindes, BPD, Farmers' Groups, Youth Organizations, Posyandu, Bumdes, PKK, Educational Institutions and Taklim assembly. The role in planning and implementing development infrastructure is primarily carried out by the village government and the Village Consultative Body. Although participation in development planning is still minimal, other institutions that act as a forum or intermediary with the government but also play a role in village development.